Is the COVID-19 lockdown nudging people to be more active: a big data analysis - Ding, D.; del Pozo Cruz, B.; Green, M. A.; Baumann, A. E. (British Journal of Sports Medicine, 2020)
The COVID-19 pandemic has brought unparalleled destruction to global health, social and economic systems. To control the spread of COVID-19, most countries have enforced a societal-level lockdown. This mass disruption of civil life provides opportunities for observational `natural experiments`, mandating lifestyle changes overnight. Big data, such as Google Trends (GT), have been used to identify outbreaks and monitor risk communication strategies, public awareness and misinformation4 during COVID-19. The real-time nature of data, together with ubiquitous internet access and Google`s dominance of online search traffic, has uniquely positioned GT as a useful tool for `nowcasting` social trends and lifestyle changes.